Meta Analysis Study of Marketing Innovation on SME Business Performance in Ethiopia - Shashi Kant; Fisseha Dejene YADETE; Chalchissa Amentie KERO (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2023)
This study looked at how market innovation affected SMEs' performance in Addis Abeba, Ethiopia, with the use of government support programs as a moderator. The study's meta-analysis will be guided by the Schumpeter innovation theory, which also incorporates the diffusion of innovation theory, expectancy theory, institutional theory, stakeholder theory, absorptive capacity theory, resource-based view/theory, dynamic capability theory, R-A theory, and a unified theory of acceptance and use of technology. The researcher used an effect size approach based on a forest and funnel plot to scan, exclude, and include relevant material. Researchers discovered a connection between the dimension of innovation and company performance on the basis of an extensive literature review. Also Based on the studied literature, the researcher discovered a link between the moderation of the government support program and the performance of SMEs' firms in the area of innovation. To carry out this study, an exploratory sequential mixed-methods research design will be used. Based on the current literature, the study attempts to create a conceptual framework and testable hypotheses. It was discovered that the impact of marketing innovation on a firm's performance was moderated by government support programs. Businesses must be encouraged to adopt government support programs with a moderating influence as a result.